2023
DOI: 10.1111/psyg.12993
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire survey of satisfaction with medication for five symptom domains of dementia with Lewy bodies among patients, their caregivers, and their attending physicians

Abstract: BackgroundThe real‐world status of satisfaction with medication for dementia with Lewy bodies (DLB) has not been elucidated. We assessed the satisfaction of patients with DLB, their caregivers, and their attending physicians (trios) with medication according to the clinical symptom domains of DLB.MethodsThis was a subanalysis of a cross‐sectional, questionnaire‐based, survey study of trios. The subanalysis set comprised analysis populations for cognitive impairment, parkinsonism, psychiatric symptoms, sleep‐re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Details of the initial study design have been reported previously (Hashimoto et al, 2022;Toya et al, 2023). This was a multicenter, crosssectional, observational survey study that included participants with DLB, their caregivers, and their attending physicians as study participants.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Details of the initial study design have been reported previously (Hashimoto et al, 2022;Toya et al, 2023). This was a multicenter, crosssectional, observational survey study that included participants with DLB, their caregivers, and their attending physicians as study participants.…”
Section: Study Design and Participantsmentioning
confidence: 99%